2020
DOI: 10.3389/fnagi.2020.571950
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Shifts in Theta Oscillatory Activity During Audio-Visual Integration Regardless of Visual Attentional Load

Abstract: Audiovisual integration (AVI) is higher in attended conditions than in unattended conditions. Here, we explore the AVI effect when the attentional recourse is competed by additional visual distractors, and its aging effect using single-and dual-tasks. The results showed the highest AVI effect under single-task-attentional-load condition than under no-and dual-task-attentional-load conditions (all P < 0.05) in both older and younger groups, but the AVI effect was weaker and delayed for older adults compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 68 publications
4
26
1
Order By: Relevance
“…Similar results were obtained using meaningless auditory/visual stimuli that removed the influence of high-order cognitive speech processes [12]. In the studies by Alsius et al [10,11] and Ren et al [12], rapid serial visual presentation (RSVP) was employed as the secondary task to add to the attentional load, which was simultaneously and temporally presented the AV discrimination task and mainly induced transient visual attention [13]. In contrast to transient attention, in which the participant was occasionally cued to the stimulated location, sustained attention requires one to maintain attention on a specific task over time, which differentially affects information perception [14,15].…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similar results were obtained using meaningless auditory/visual stimuli that removed the influence of high-order cognitive speech processes [12]. In the studies by Alsius et al [10,11] and Ren et al [12], rapid serial visual presentation (RSVP) was employed as the secondary task to add to the attentional load, which was simultaneously and temporally presented the AV discrimination task and mainly induced transient visual attention [13]. In contrast to transient attention, in which the participant was occasionally cued to the stimulated location, sustained attention requires one to maintain attention on a specific task over time, which differentially affects information perception [14,15].…”
Section: Introductionsupporting
confidence: 78%
“…To study the effect of visual attentional load on AVI, Alsius et al instructed participants to conduct the classic McGurk test under low (single task) and high (dual task) attentional load conditions, and both behavioral and EEG results showed decreased AVI under high attentional load conditions than under low attentional load conditions [10,11]. Similar results were obtained using meaningless auditory/visual stimuli that removed the influence of high-order cognitive speech processes [12]. In the studies by Alsius et al [10,11] and Ren et al [12], rapid serial visual presentation (RSVP) was employed as the secondary task to add to the attentional load, which was simultaneously and temporally presented the AV discrimination task and mainly induced transient visual attention [13].…”
Section: Introductionmentioning
confidence: 93%
“…(2011) , Ren et al. (2016) , and Ren, Li, et al. (2020) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, compared with younger adults, the visual acuity was lower and the auditory threshold was higher in older adults ( Cliff et al., 2013 ; Grady, 2009 ; Liu & Yan, 2007 ; Spear, 1993 ), and this deterioration leads to poorer health status and cognitive functional decline in older adults ( Freiherr et al., 2013 ). Although some studies reported a decreased AVI for older adults compared with younger adults ( Mahoney et al., 2011 ; Ren, Li, et al., 2020 ; Ren et al., 2016 , 2018 ; Wu et al., 2012 ) resulting from age-related general cognitive functional decline, numerous studies also found a higher AVI for older adults than for younger adults ( Deloss et al., 2013 ; Laurienti et al., 2006 ; Peiffer et al., 2007 ; Sekiyama et al., 2014 ; Zou et al., 2017 ). Neuroimaging studies further proposed that older adults might recruit new brain networks ( Diaconescu et al., 2013 ; Ren et al., 2018 ; Ren, Li, et al., 2020 ; Ren, Xu, et al., 2020 ) and strengthen global brain connectivity ( Wang et al., 2018 ) during audiovisual information processing, indicating that it is an adaptive mechanism.…”
mentioning
confidence: 99%
See 1 more Smart Citation